Spirituality and Self-efficacy: A Comparison between College and Madāris Students (Al-Qamar, 2019)
The current study is aimed to investigate the differences between spirituality and self-efficacy in college and madāris students. Survey research design is used. Sample is selected through non-probability purposive sampling strategy. 100 students were recruited from government colleges of Shāīwāl division and 100 from registered madāris of Shāīwāl division. Multidimensional Measure of Islamic Spirituality and General Self-efficacy Scale were used to collect data. T-test analysis revealed statistically significant differences of spirituality and self-efficacy between college and madāris students. Madāris students showed higher level of spirituality and self-efficacy. The findings of the present study will help educationists to broad the scope of general education in order to strengthen the personalities of students in government colleges.